TNF alpha signaling is associated with therapeutic responsiveness to vascular disrupting agents in endocrine tumors. (5th March 2016) - Hantel, Constanze; Ozimek, Alexandra; Lira, Regia; Ragazzon, Bruno; Jäckel, Carsten; Frantsev, Roman; Reincke, Martin; Bertherat, Jérôme; Mussack, Thomas; Beuschlein, Felix
Abstract: ASA404 (Vadimezan) belongs to a class of agents with disrupting properties against tumor vasculature, which is partly mediated by TNFα-signaling. Preclinical and early clinical studies have indicated promising results for ASA404, while extended clinical trials performed poorly. Our aim was to investigate the potential therapeutic applicability of ASA404 against endocrine tumors. Moreover, as the reason for the unpredictable clinical anti-tumor activity of ASA 404 remained uncertain in previous studies, we compared two tumor models of endocrine origin with different responses to ASA404 treatment. Specifically, we determined anti-tumoral effects in preclinical models of neuroendocrine tumors of the gastroenteropancreatic system (BON) and adrenocortical cancer (NCI-H295R) in vitro and in xenograft models in vivo . Upon treatment of tumor bearing mice significant anti-tumoral effects, an increase in TNFα as well as activation of TNFα-specific downstream signaling were evident in the BON tumor model while no comparable effects were detectable for NCI-H295R. We identified TNFAIP3/A20, a key molecule of an inhibitory feedback-loop downstream of TNF-receptor 1, CD40, Toll-like receptors, NOD-like receptors and the interleukin-1 receptor signaling cascades, as overexpressed in the adrenocortical carcinoma tumor model. Subsequent analyses of clinical patient samples confirmed a correlation between tumor TNFAIP3 expression levels and overall survival in patients with ACC. Taken together our findings provide evidence that modulation of TNFα-signaling could be of relevance both for the clinical course of ACC patients and as a marker of treatment response. Highlights: We compare two models for endocrine tumors with different therapeutic responsiveness. We identified TNFAIP3/A20 as overexpressed in the therapy-resistant tumor model. We reveal a correlation between TNFAIP3 expression and survival in human ACC samples.